Entre a nação e a região: os Institutos Históricos e Geográficos do Pará e do Amazonas na escrita da História do Brasil, a partir da Amazônia (1917-1953) - BARROS, Lucilvana Ferreira dos Santos (Universidade Federal do Pará, 2025)
This doctoral dissertation aims to analyze the role of the Historical Geography Institutes of the states of Pará and Amazonas, as well as their members, in the construction of the historiographical field of the Amazon and its inclusion into the history of Brazil between 1917 and 1953. The objective of this research is to understand the intentions, strategies, and historical context in which this field operated, especially in the relations between region and nation. In order to assess the activities of the institutions and their historians in the creation of the regional historiographical field, an investigation was carried out based on those institutes’ journals, charters, minutes, letters, correspondence, newspaper articles, reports and proceedings of the National History Congresses held by the Brazilian Historic and Geographic Institute (IHGB), books, book chapters, and articles. This dissertation was founded – theoretically and methodologically – on Pierre Bourdieu’s notion of Fields, especially that of Intellectual Field and its connection with the Field of Power. The initial reading of the documents, as well as the theoretical and methodological framework used in this analysis, allowed for the understanding of the construction of a regional historiographical field. This was disseminated through publications, sent and received correspondence, participation in events, among other mechanisms, that emphasized Amazonian events, characters and narratives in dialogue with the Brazilian history, especially those of founding narratives, both regional and national, the biography of the great names in the history of Brazil and the Amazon, the regional economy, the history of cities and states, the culture, the land and the man of the Amazon, among other themes. The main argument aims to demonstrate that from the formation of a regional historiographical field there was not a process of closing this field around the history of the Amazon, but, rather, a process of writing the History of Brazil starting in the Amazon. Therefore, it is argued that the History of Brazil was not written solely by the IHGB. It was also written from regional spaces, the contact zones among those institutions, in particular due to the struggles seen in historiography in the representations and negotiations of the intricate relations between region and nation.